New-institutional analysis of gender issue: Paradox & unwanted effects - Sánchez-Bayón, Antonio (DIXI, 2023)
This is a critical neoinstitutionalist review from comparative political economy approaches and heterodox approaches, in order to understand and evaluate the gender issue and its unintended effects, such as the gender paradox. It turns out that the more gender regulation has advanced, especially that inspired by trans feminism (of sociocultural construction and self-perception feeling), it seems to have decreased the level of legal guarantees for cis women (of coincident biological and genetic basis), besides causing the perverse effect of turning the autonomy achieved into state dependence. A presentation of the problem is addressed with a historical, comparative and narrative review, and it is clarified how feminism has imposed itself, hiding suffragism and other women’s rights movements. It continues with a refutation of gender fallacies, from the study of their production in the Anglo-Saxon and Nordic world to their distribution from un-Women and the fifth generation of human, gender and ethnocultural rights. Finally, attention is focused on a case of transplantation of the matter, such as the Spanish case, and the “undesired effects” of its recent regulation are evaluated, as well as the aforementioned paradox. Conclusions and future lines of research complete the paper.